Nitric oxide regulation of leaf phosphoenolpyruvate carboxylase-kinase activity: implication in sorghum responses to salinity - Monreal, José A. (2013)
Nitric oxide (NO) is a signaling molecule that mediates many plant responses to biotic and abiotic stresses, including salt stress. Interestingly, salinity increases NO production selectively in mesophyll cells of sorghum leaves, where photosynthetic C4 phosphoenolpyruvate carboxylase (C4 PEPCase) is located. PEPCase is regulated by a phosphoenolpyruvate carboxylase-kinase (PEPCase-k), which levels are greatly enhanced by salinity in sorghum. This work investigated whether NO is involved in this effect. NO donors (SNP, SNAP), the inhibitor of NO synthesis NNA, and the NO scavenger cPTIO were used for long- and short-term treatments. Long-term treatments had multifaceted consequences on both PPCK gene expression and PEPCase-k activity, and they also decreased photosynthetic gas-exchange parameters and plant growth. Nonetheless, it could be observed that SNP increased PEPCase-k activity, resembling salinity effect. Short-term treatments with NO donors, which did not change photosynthetic gas-exchange parameters and PPCK gene expression, increased PEPCase-k activity both in illuminated leaves and in leaves kept at dark. At least in part, these effects were independent on protein synthesis. PEPCase-k activity was not decreased by short-term treatment with cycloheximide in NaCl-treated plants; on the contrary, it was decreased by cPTIO. In summary, NO donors mimicked salt effect on PEPCase-k activity, and scavenging of NO abolished it. Collectively, these results indicate that NO is involved in the complex control of PEPCase-k activity, and it may mediate some of the plant responses to salinity.